Analysis of Determinants of Student Decisions in Choosing the Economic Education Study Programme in Support of SDG 4 - Raafika Tri Seloumita; Riza Yonisa Kurniawan (Journal of Psychology and Culture Behavior in SDGs, 2026)
Objective: This research aims to analyse the partial and simultaneous effects of various external and internal determinants that influence the decision to choose an economics education study programme at university. Method: A quantitative approach was used to analyse the relationship between variables. Sampling was conducted using purposive sampling with the assistance of online questionnaires distributed to students of Universitas Negeri Surabaya. The data analysis technique involved multiple linear regression with the help of SPSS. Results: Interest in the subject, family support, career opportunities, skills and mastery of the material, and academic challenges have a positive and significant effect both partially and simultaneously on deciding on a study programme. Novelty: This research presents a new model of internal and external determinants that influence the choice of economics education study programmes among students, which is rarely encountered. In addition, there is a recent contribution that the adjustment of the economics education curriculum must be able to differentiate the broad employment prospects of graduates and the comfort of learning.